استخدام تفل الزيتون لإنتاج غراس الغار النبيل L. Laurus nobilis والصنوبر الثمري Pinus pinea L. في المشاتل بمحافظة اللاذقية - علاء الدين, حسن; زريقة, هبة (Latakia University Journal -Biological Sciences Series, 2017)
أجريت هذه الدراسة خلال الفترة 2014-2016 م في مشتل كلية الزراعة جامعة تشرين، وقد هدفت هذه الدراسة إلى حساب نسبة إنبات بذور الغار والصنوبر الثمري باستخدام نسب مختلفة من تفل الزيتون مع خلطة المشتل, ودراسة بعض خصائص الغراس الناتجة وكذلك بعض الصفات الفيزيائية والكيميائية للخلطات الزراعية المستخدمة, وتم تحليل النتائج الحاصلة باستخدام البرنامج الإحصائي spss: تم خلط تربة المشتل (رمل, تربة 1:1) مع تفل الزيتون بنسب (25,50,75,100)% وتم تقدير: نسبة الإنبات، الوزن الرطب والجاف للمجموعين الخضري والجذري، الوزن الحجمي، رطوبة الوسط والخصائص الكيميائية، حيث أظهرت النتائج أن نسبة الإنبات قد تزايدت في كل من بذور الغار والصنوبر الثمري بزيادة نسبة التفل في الوسط الزراعي بشكل عام، وعلى العكس فقد تزايد الوزن الرطب للمجموع الخضري مع تناقص نسبة تفل الزيتون في كلا النوعين المدروسين. بالنسبة للخصائص الفيزيائية تناقص الوزن الحجمي للأوساط الزراعية المدروسة بزيادة نسبة تفل الزيتون، كما ازدادت نسبة رطوبة التربة بزيادة نسبة التفل. أما فيما يخص الخصائص الكيميائية فقد لوحظ غنى الأوساط الزراعية المستخدمة الحاوية على تفل الزيتون بالعناصر المعدنية (حديد, مغنزيوم ونحاس)، وبقيت الملوحة والحموضة ضمن الحدود الطبيعية، لذلك فقد برهنت الدراسة على صلاحية استخدام تفل الزيتون كوسط للزراعة بشكل كامل أو ضمن الخلطات الزراعية المستخدمة في المشاتل.This study was conducted during the period 2014-2016 in the nursery College of Agriculture, University of Tishreen, this study aimed to calculate the percentage of germination of the seeds of Laurus nobilis and Pinus pinea using different proportions of olive cake with a mixture Arboretum, and study some of the planter resulting properties as well as some physical and chemical characteristics of agricultural mixture that used. were analyzed using spss statistical program The mixing nursery soil (sand, soil 1: 1) with olive cake rates (25,50,75,100)% . assessment: germination percentage, wet and dry weight of shoot and root grouped, volumetric weight, moisture middle and chemical characteristics. , For germination percentage it has increased every germination of seeds of laurel and pine fruiting increase the proportion of bagasse in the agricultural center in general ratio, and on the contrary has increased wet weight of shoots with decreasing proportion of olive cake in both types studied. For the physical properties there was a decrease in the volumetric weight of the agricultural community to increase the proportion of the studied olive cake, as soil moisture ratio increased to increase the proportion of bagasse. Rich agricultural circles used container Regarding chemical properties have been observed on the olive cake metal elements (iron, magnesium and copper), The salinity and acidity remained within normal limits, so the study has demonstrated the validity of the use of olive cake as a medium for planting in whole or in part agricultural mixtures used in nurseries.